Plan de marketing para el almacén de electrodomésticos “Créditos Pillajo” de la ciudad de Nueva Loja, provincia de Sucumbíos - Alcívar Ruiz, Inés Elizabeth (2014)
This paper address the issue "DEVELOPMENT MARKETING PLAN FOR STORE APPLIANCE" CREDITS PILLAJO "The overall goal was to develop a marketing plan for appliances store credits Pillajo city of Nueva Loja, through situational analysis, internal and external analysis. To research the historical, deductive, inductive and Statistical and Analytical methods are used; and techniques of direct observation, interview and survey manager at both 7 employees and a sample of 299 customers, data collection was taken from primary and secondary sources. According to the evaluation of external factors (EFE) was obtained as weighted value 2.97 and by evaluating internal factors (EFI) is the weighted score of 2.66 determined, saying it has strengths that outweigh its weaknesses. Based on the SWOT matrix was constructed high impact, the same that was used to propose a mission, vision and corporate values, at the junction of the variables were five strategic objectives, which are detailed in the proposal, it is noted that Qualitative Matrix according to respective budgets are: $4.226 planning options with their respective budgets. Among the findings it was mentioned that the Warehouse Appliances "Credits Pillajo" does not have a marketing plan that best allows the service offering has advantage of their strengths and opportunities as the wide variety of products and the guarantee offered in themselves and their main weakness as inefficient customer service. That is why the use of Marketing Stated Plan is recommended and for that we need a budget required for the implementation of operational. Finally it is recommended to implement the marketing plan proposed in this study, pay attention to the changing needs of customers, spread the mission, vision among the employees of the organization, maintain policy affordable and fund the marketing plan preferably with equity of the company.